Aplikasi metode regresi logistik biner sebagai model keberhasilan belajar - Gandhi Pawitan (Jurnal Administrasi Bisnis, 2009)
Success or fail in a study at university can be affected by some factors. Entry selectionprocess can be an initial stage in success prediction, up to graduation. Have theentry selection examination detected this appropriately ? Or have other evaluationmechanism within their study set early warning ? These are a focus question in thisarticle.According to academic data of year 1998 through 2006, found that entry selectionexamination give a prediction of success proportion of student finishing theirstudy. Meanwhile their second semester grade point academic gave a significant indicationof the success and failure. And also found that second semester grade pointacademic had a significant contribution for their achievement in first stage evaluationresult at fourth semester.Keywords: logistic regression, correlation analysis